Investigating 4th year pre-service teachers’ levels of understanding of the disciplinary nature of Life Sciences as a discipline - Xaba, Nomzamo (My University, 2017)
Disciplinary knowledge is recognised as teacher professional knowledge base that is central in promoting effective teaching and learning in science education. Although that is the case, in one of the South African University, that this study was conducted in, the 4th year Life sciences Pre-service teachers’ were not tested on their understanding of the disciplinary nature of their subject of specialisation. As a result, the type of disciplinary gaze that they acquired by the end of the teacher training remained unknown within the institution. Thus, this study then used a case study methodology to investigate the Pre-service teachers’ levels of understanding of the disciplinary nature of Life Sciences as a discipline. The participants of this study consisted of twenty nine 4th year Pre-service teachers’ who were enrolled for a Life sciences Bachelor of Education program and one Life sciences lecturer who was involved in teaching the subject. This research took on a qualitative approach, which yielding both qualitative and quantitative data, through the use of questionnaires as well as semi-focused interviews as research instruments. The outcomes of this study showed that, although the Pre-service teachers’ were not explicitly taught about the nature of the subject, but they still showed a satisfactory understanding of it. Although that was the case, the Pre-service teachers’ still demonstrated a fractured comprehension of the disciplinary knowledge aspects, such as the history, philosophy and the nature of science. On the other hand, the findings of this study also demonstrated that, the Pre-service teachers’ acquired an extensive gaze of understanding of Subject Matter Knowledge, which is another component of Disciplinary knowledge, and this was because, this knowledge base was explicitly taught and assessed with the teacher training program.
A research report submitted to the faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Masters of Science. 20 July 2017.
Keywords: Life sciences--Study and teaching; Biology--Study and teaching (Higher)--South Africa; Education, Higher--South Africa; Teachers--Training of; Science teachers--In-service training--South Africa